MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN RADEC (READ, ANSWER, DISCUSS, EXPLAIN, CREATE) PADA PEMBELAJARAN IPA KELAS VC SDN MENTENG ATAS 14 JAKARTA SELATAN - Ari Nirwana; Endang Wahyudiana; Yofita Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This classroom action research aimed to improve science learning outcomes through the RADEC (Read, Answer, Discuss, Explain, Create) learning model among students of Class VC at SDN Menteng Atas 14, South Jakarta. The study was conducted to determine the effectiveness of the RADEC learning model, with the success indicator being an improvement in students’ learning outcomes in science. The research subjects were 22 students in Class VC, consisting of 11 male and 11 female students. The study employed the cyclical model of Kemmis and McTaggart, which involves the stages of planning, implementation, observation, and reflection. The success criteria of the study were met if 80% of students reached the Minimum Learning Mastery Criteria (KKTP), which was set at 75, and if 80% of the RADEC model implementation was achieved. In Cycle I, the percentage of students who achieved cognitive learning mastery was 68%, indicating that the criteria had not yet been met. In Cycle II, this percentage increased to 86%, showing significant improvement. The observation instruments for teacher and student activities during Cycle I showed implementation rates of 80% and 85% in the first and second meetings, respectively. In Cycle II, these rates increased to 85% in the first meeting and 95% in the second meeting. The implementation of the RADEC learning model can be considered an effective approach to enhance science learning outcomes among fifth-grade elementary school students, as it is student-centered and actively engages learners in meaningful learning experiences to understand the subject matter.